ANALISIS PENGARUH TINGKAT LABA BERSIH DAN UKURAN PERUSAHAAAN TERHADAP KOEFISIEN RESPON LABA PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2013 - 2016 - Soei, Reynaldo Soeiswanto; Nangoi, Grace B.; Kalalo, Meily Y. B. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The earnings response coefficient can be indicated as the ability of the profit information to respond to the market. In other words, reported earnings have the power of response. The purpose of this research was to analyze the influence of net profit rate and size firm on earnings response coefficient. The population of this research is manufacturing companies listed on Indonesia Stock Exchange in period 2013-2016 as many as 149 companies. From the population of 149 manufacturing companies listed on Indonesian Stock Exchange, researchers used a sample of 36 manufacturing companies. The independent variables are net profit rate and size firm while the dependent variable is earnings response coefficient. The analysis method of this research are quantitative descriptive statistics and multiple linear regression analysis. The result of normality test showed that the independent variabel and the dependent variabel are not normally distributed. When the data is not normally distributed, the thing to do is transform the research data and test the normality again. The result of this research showed that net profit rate has positive and not significant effect on earnings response coefficient, size firm has positive and significant effect on earnings response coefficient, and also net profit rate and size firm have significant result on earnings response coefficient.Keywords : Net Profit Rate, Size Firm, Earnings Response Coefficient